Interaction of Nitroxide Radicals with an au8 Nanostructure: Theoretical and Calorimetric Studies - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Pastenes, C (American Chemical Society, 2019)
Nitroxide radicals, adhered to gold nanoparticles, have found novel applications such as cancer treatment, neuroprotection after cerebral injury, radiotherapy, and as drug-delivering agents. The details of the nature of the binding of nitroxide radicals to metallic nanostructures have been a subject of debate for the last two decades. In this work, microcalorimetric measurements are complemented with a theoretical study of noncovalent interactions between different derivatives of the nitroxide radical 2,2,5,5-tetramethylpiperidinoxyl and an Au8 nanocluster to shed light on the nature of the binding of the radical molecule and the nanocluster. Experiments and theory showed that, although the molecule could bind through the nitroxide group, organic substituents such as amino and carboxyl groups interact much more favorably with the nanocluster. Attachment of these groups to the gold nanocluster is the result of an intense polarization of the "nucleophilic" sites of the metallic cluster, strengthened by van der Waals attraction between the molecule and the nanocluster. Copyright © 2019 American Chemical Society.